How Shifts in Economic Policy Affect Infrastructure Firm Performance ? (Jurnal Manajemen Bisnis, 2023)
This quantitative research was conducted on companies in the infrastructure sector in Indonesia, Singapore, the Philippines, and Vietnam to see a comparison of economic policies in influencing company performance, the progress of the infrastructure sector, and good implementation in each country. The company performance measurement variables used are ROE and ROA. This research was conducted in a prescriptive way by collecting secondary data from official stock exchange sites, namely the Indonesia Stock Exchange (IDX), Singapore Exchange Limited (SGX), Philippine Stock Exchange (PSE), and Hanoi Stock Exchange (HNX). To find out the relationship between variables, analysis, and data processing in this study we used the Vector Autoregressive (VAR) method. The results of this study are that the economic policies implemented by each country have different impacts according to the economic conditions in the country so they have different impacts on the implementation of monetary and fiscal policies. In Indonesia and the Philippines, the impact of interest rate monetary policy can significantly affect company performance (positive effect), while in Vietnam and Singapore, it is not proven to have a significant effect. In Indonesia and the Philippines, the impact of fiscal policy shows that the performance of companies in the infrastructure sector appears to be positively influenced by the State Budget and IR, but in Vietnam and Singapore, it does not appear to be positively affected.